Clinical benefits of the 5th intercostal incision in uniportal VATS for female patients - Dalin Wang; Zhilin Luo; Jia Ming (Scientific Reports)
Abstract To assess the clinical benefits of a 5th versus 4th intercostal incision in female patients undergoing uniportal video-assisted thoracoscopic surgery (VATS) lobectomy and lymphadenectomy, focusing on breast tissue preservation, pain, cosmetic outcomes, recovery, and surgical maneuverability. A retrospective analysis of 150 female lung cancer patients was conducted, divided into 4 and 5th intercostal incision groups (n = 75 each). Propensity score matching balanced baseline characteristics. Primary outcomes included breast tissue involvement, postoperative pain (VAS), cosmetic satisfaction (Likert scale), recovery time, surgical maneuverability, and complication rates. Statistical analysis used Mann-Whitney U and Chi-square tests for group comparisons and multivariable regression to adjust for confounders. The 5th intercostal incision significantly reduced breast tissue involvement (10.7 vs. 65.3%, p < 0.01), postoperative pain (VAS: 4.8 vs. 7.2, p < 0.01), and recovery time (5.9 vs. 8.4 days, p < 0.05), while enhancing cosmetic satisfaction (p < 0.01) and improving access to upper pulmonary veins. Incision site infections were notably lower in the 5th intercostal group (2.7 vs. 10.7%, p < 0.05). The 5th intercostal incision provides substantial clinical advantages in uniportal VATS for female patients, including reduced breast tissue involvement, minimized pain, enhanced cosmetic outcomes, and faster recovery. These findings support the 5th intercostal incision as a preferred approach in this patient population, aligning with precision surgery principles to optimize outcomes.